2016
DOI: 10.1039/c6sc00584e
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine coated shape memory polymer: enabling light triggered shape recovery, light controlled shape reprogramming and surface functionalization

Abstract: Simple dip-coating transforms thermally responsive shape memory polymers into photo-responsive materials and allows for shape engineering and surface functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 41 publications
3
99
0
1
Order By: Relevance
“…[29] To investigate whether the lattice contraction that occurs when 1 is transformed to 1A is able to produce am easurable macroscopic change,along single crystal of 1 (0.11 0.13 2.62 mm) was irradiated with UV light and the physical appearance of the crystal was moni- Figure 2a and in the Supporting Information, Movie S1. Further irradiation experiments revealed that the generation of the right-handed helix morphology was independent of the direction of the light source.T he rapid and substantial change in the crystal shape (808 8 s À1 )i sattributed to the lattice contraction of 6.1 %upon irradiation and is in contrast to photoresponsive shapememory polymer-based actuators [30] that exhibit as lower mechanical response upon irradiation. Thec rystal then rapidly twisted into the right-hand helical shape within 15 seconds as the photoreaction involving the dimerization of coordinated 3-F-spy ligands transforms the 2D structure of 1 to the interpenetrating 3D structure of 1A.N oticeably,t he crystal retained its helical morphology when the light is switched off (Supporting Information, Figure S14).…”
mentioning
confidence: 99%
“…[29] To investigate whether the lattice contraction that occurs when 1 is transformed to 1A is able to produce am easurable macroscopic change,along single crystal of 1 (0.11 0.13 2.62 mm) was irradiated with UV light and the physical appearance of the crystal was moni- Figure 2a and in the Supporting Information, Movie S1. Further irradiation experiments revealed that the generation of the right-handed helix morphology was independent of the direction of the light source.T he rapid and substantial change in the crystal shape (808 8 s À1 )i sattributed to the lattice contraction of 6.1 %upon irradiation and is in contrast to photoresponsive shapememory polymer-based actuators [30] that exhibit as lower mechanical response upon irradiation. Thec rystal then rapidly twisted into the right-hand helical shape within 15 seconds as the photoreaction involving the dimerization of coordinated 3-F-spy ligands transforms the 2D structure of 1 to the interpenetrating 3D structure of 1A.N oticeably,t he crystal retained its helical morphology when the light is switched off (Supporting Information, Figure S14).…”
mentioning
confidence: 99%
“…[ 25 ] Up to date, the PDA polymer material has been applied in various research fields due to its versatility and programmability. [ 26–29 ] Interestingly, it was found that the PDA nanospheres and coatings can act as effective photothermal materials showing strong absorption at NIR region with high photostability, [ 30,31 ] which makes the PDA polymer a promising candidate in multiple applications like photothermal therapeutic agent for cancer therapy, [ 30,32 ] fabrication of the programmable shape‐memory materials, [ 31,33 ] and shape‐morphing of liquid metals. [ 34 ] Based on the versatile PDA coating, herein, a NIR‐responsive polymeric oscillator was judiciously designed and fabricated by selectively depositing a PDA layer on the splay‐aligned LCN films.…”
Section: Figurementioning
confidence: 99%
“…Through the thickness of the film, the director of the liquid crystals gradually changes from planar to homotropic. The PDA‐coated LCN film was obtained by immersing blank film into the aqueous solution containing dopamine hydrochloride and Tris base for 24 h. [ 31,35,36 ] After PDA treatment, the appearance of the LCN film became black from transparent. The X‐ray photoelectron spectroscopy (XPS) illustrates the increase of N element on the surface when the blank LCN film was coated by PDA layer (Figure S2, Supporting Information).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Zhen et al. reported a polydopamine coated shape memory polymer which enable the light triggered shape recovery, light controlled shape reprogramming and surface functionalization of polymers . Ji et al.…”
Section: Introductionmentioning
confidence: 99%